Esterified sago waste for engine oil removal in aqueous environment - Zainab, Ngaini; Farid, Noh; Rafeah, Wahi (Taylor & Francis, 2014)
Agro-waste from the bark of Metroxylon sagu (sago) was studied as a low cost and effective oil sorbent in dry and aqueous environments. Sorption study was conducted using untreated sago bark (SB) and esterified sago bark (ESB) in used engine oil. Characterization study showed that esterification has successfully improved the hydrophobicity, buoyancy, surface roughness and oil sorption capacity of ESB. Sorption study revealed that water uptake of SB is higher (30 min static: 2.46 g/g, dynamic: 2.67 g/g) compared withESB(30 min static: 0.18 g/g, dynamic: 0.14 g/g). ESB, however, showed higher oil sorption capacity in aqueous environment (30 min static: 2.30 g/g, dynamic: 2.14) compared with SB (30 min static: 0 g/g, dynamic: 0 g/g). ESB has shown great potential as effective oil sorbent in aqueous environment due to its high oil sorption capacity, low water uptake and high buoyancy.